Accuracy of leukocyte esterase reagent strip test and platelet indices for early diagnosis of ascitic fluid infection in liver cirrhosis - Dutta, Rajib; Rahman, Mohammad M.; Patwary, Rezaul I.; Imam, Iftekhar; Ahmad, Habib I.; Choudhury, Shusmita D.; Datta, Indrajit K.; Bhuiyan, Tareq M. (International Journal of Advances in Medicine, 2023)
Background: Spontaneous bacterial peritonitis (SBP) is one of the serious complexities in patients with cirrhosis and ascites. 30-50% of death may occur if it not treated properly. The leucocyte esterase reagent (LER) strip test is a special apparatus for prior detection of neutrophils in the ascetic fluid. The aim of the study was to investigate the diagnostic accuracy of the LER strip test and platelet indices in the early detection of SBP in cirrhotic patients. Methods: This cross-sectional study was carried out in the department of gastrointestinal hepatobiliary and pancreatic disorders (GHPD), BIRDEM, Dhaka, Bangladesh, from January 2018 to October 2019. A total of 110 indoor patients of liver cirrhosis with ascites were enrolled after fulfilment of the inclusion and exclusion criteria with adequate history taking and clinical examination. Results: Out of 110 cases, 68 were male and 42 were female, and among them 23 (20.9%) patients had SBP. LER strip test at grade 4 set as a cut-off value which showed sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy was 91.3%, 90.8%, 70%, 97.5%, and 90% respectively. Mean platelet volume (MPV) and platelet distribution width (PDW) were done by complete blood count, where the MPV cut-off value set as 12.5 fl showed sensitivity, specificity, PPV, NPV, and accuracy were 82.6%, 90.8%, 66%, 96.25%, and 88.18% respectively. PDW cut-off value set on 18.10% revealed sensitivity, specificity, PPV, NPV, accuracy was 82.6%, 83.9%, 50%, 95.71% and 79% respectively. ROC curve was plotted to set the cut-off value by examining sensitivity and specificity. Results were considered statistically significant at p<0.05. Conclusions: This study was undertaken to detect LER strip tests that showed significant results in bedside diagnosis of SBP. Apart from this, a significant increase in MPV and PDW was observed in SBP. So, LER strip tests and platelet indices measurement can be economical and reliable appliances for early diagnosis of SBP.